2008
DOI: 10.1111/j.1440-1681.2008.04927.x
|View full text |Cite
|
Sign up to set email alerts
|

Subendocardial Viability Ratio Estimated by Arterial Tonometry: A Critical Evaluation in Elderly Hypertensive Patients With Increased Aortic Stiffness

Abstract: 1. Increased aortic stiffness predisposes to myocardial ischaemia by increasing the systolic tension-time index and by decreasing aortic pressure throughout diastole. The tonometric subendocardial viability ratio (SEVR) is a non-invasive estimate of myocardial perfusion relative to cardiac workload. The hypothesis that SEVR is impaired in elderly hypertensives with high aortic pulse pressure (PP) was tested in the present study. 2. The SEVR was calculated by radial applanation tonometry in 203 subjects. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 28 publications
2
46
0
3
Order By: Relevance
“…26,32 Ferro et al 27 showed a close relation between ischemic threshold and degree of coronary stenosis during diastolic perfusion time, but no correlation was found when explored throughout the whole cardiac cycle. In a recent invasive study, Chemla et al 30 confirmed these observations and showed that diastolic time/left ventricular ejection time ratio is the main factor affecting SEVR and is responsible for 81% of the variability of SEVR in resting humans.…”
Section: Subendocardial Viability Ratiosupporting
confidence: 59%
See 1 more Smart Citation
“…26,32 Ferro et al 27 showed a close relation between ischemic threshold and degree of coronary stenosis during diastolic perfusion time, but no correlation was found when explored throughout the whole cardiac cycle. In a recent invasive study, Chemla et al 30 confirmed these observations and showed that diastolic time/left ventricular ejection time ratio is the main factor affecting SEVR and is responsible for 81% of the variability of SEVR in resting humans.…”
Section: Subendocardial Viability Ratiosupporting
confidence: 59%
“…14,30,31 The importance of diastolic perfusion time as a determinant of subendocardial perfusion has been well demonstrated in experimental studies. 26,32 Ferro et al 27 showed a close relation between ischemic threshold and degree of coronary stenosis during diastolic perfusion time, but no correlation was found when explored throughout the whole cardiac cycle.…”
Section: Subendocardial Viability Ratiomentioning
confidence: 99%
“…Finally, the calculation of the tonometric SEVR was as provided by the manufacturer and did not include a non-invasive estimate of LV enddiastolic pressure as it is required in patients known or suspected to exhibit elevated LV filling pressure. 30,31 However, none of the studied patients exhibited E/Em values 415, which constitutes a consistent index of increased LV filling pressures.…”
Section: Coronary Flow Reserve and Buckberg Index D Tsiachris Et Almentioning
confidence: 86%
“…In particular, diastolic time fraction is a determinant of both SEVR and coronary flow increase when the autoregulatory mechanism is exhausted because larger fractional diastolic time occurs at lower perfusion pressure, in the presence as well as in the absence of coronary stenosis. 6,14,[30][31][32][33] Alternatively, impaired CFR may provoke diastolic dysfunction as it has been shown that delayed myocardial relaxation associated with less early diastolic filling due to ischaemia occurs early in the setting of reduced CFR before evidence of wall motion abnormalities. 26 The current study is cross-sectional; therefore, causation cannot be determined for any of the observed relationships.…”
Section: Coronary Flow Reserve and Buckberg Index D Tsiachris Et Almentioning
confidence: 99%
“…Thus, it can be a comprehensive determinant of the cardiac afterload against the pulsatile blood flow. TAC decreases in response to increased arterial stiffness (e.g., due to aging) and is reported to be associated with essential hypertension [27] and the myocardial oxygen demand-supply balance [28].…”
Section: Total Arterial Compliancementioning
confidence: 99%